(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The clinico-epidemiological data of 276 childhood psoriasis were studied. The mean age was 7.64 years (range 1 day to 15 years). There was no complain of any discomfort in 198 cases. Itching was present in 67 cases and burning in 11 cases. Plaque psoriasis was the most common type (68.8%) followed by guttate (18.8%). Erythrodermic and pustular psoriasis were found in 2.2% and 1.5% cases. Scalp was the most frequently affected site (75.36%) followed by extensors of extremities (41.3%), trunk (37.7%), palm and/or sole (13.0%) and diaper area (11.6%). Nail involvement was found only in 8%, joint was affected in 3.6% and only 2.2% children with psoriasis were erythrodermic. In Bangladeshi children with psoriasis, plaque is the most common type and scalp is the mostly affect site. Nail and joint involvement is less common. Pustular and erythrodermic psoriasis is rare.